Heavy metal pollution in agricultural soils of a typical volcanic area: Risk assessment and source appointment. (October 2022) - Yang, Jianzhou; Sun, Yanling; Wang, Zhenliang; Gong, Jingjing; Gao, Jianweng; Tang, Shixin; Ma, Shengming; Duan, Zhuang
Abstract: Heavy metals are naturally occurring elements with high natural background levels in the volcanic area. Therefore, it is necessary to conduct a risk assessment and identify potential sources of heavy metals. In this study, 4488 soil samples (0–20 cm) were collected in Chengmai County, a typical volcanic area in Hainan Province, and analyzed for eight heavy metals and major oxides. Pollution level, ecological risks, and health risks were evaluated by geo-accumulation index ( I geo ), pollution index ( PI ), potential ecological risk index ( RI ), hazard index ( HI ), and carcinogenic risks ( CR ). The positive matrix factorization ( PMF ) model was further used to determine the priority source of heavy metals. The average values of heavy metal concentrations in soil were 7.06, 0.07, 156.88, 33.43, 0.05, 72.47, 19.48, and 67.51 mg kg −1 for As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn, respectively. Except for Pb, the average concentrations of all heavy metals exceeded background concentration in Hainan soils, indicating different degrees of heavy metal enrichment. The I geo and PI showed that the main pollutant element in volcanic soils was Ni, followed by Cr and Cu. The RI shows that the percentage of soil samples with considerable or worse potential ecological risk was 44.4% of the total samples, with Hg, As, Cd, and Ni causing high ecological risks. The estimated average daily doses of heavy metals were below the tolerable limits and the HI values were below one for both adults and children, indicating that the residents had an acceptable potential non-carcinogenic risk. However, the potential carcinogenic risk of exposure to Cr, Ni, and As was unacceptable for residents, with high CR values exceeding 10 −4, especially for children. Based on the PMF, five major sources of heavy metals were found in the study area: Ni, Cu, and Zn mainly from parent materials, As and Pb from daily life and vehicle emissions, Cd from agricultural activities, Hg from industrial activities, and Cr from parent materials under different environmental conditions. Significant positive correlations between Al2 O3, TFe2 O3, Mn, soil organic carbon (SOC), and heavy metals reflect that aluminium-rich minerals, Fe–Mn oxides, and SOC are the most critical factors affecting heavy metal accumulation in volcanic agricultural soils. Graphical abstract: Image 1 Highlights: A comprehensive heavy metal pollution, ecological risk, and health risk assessment of agricultural soils in the volcanic area was conducted. The potential carcinogenic risk of Cr, Ni, and As exposure in the study area was unacceptable to residents. High concentrations of Ni, Cr, Zn, and Cu in the volcanic agricultural soils were attributed to natural processes. Al-rich minerals, Fe-Mn oxides, and SOC are the main factors of heavy metal accumulation in volcanic agricultural soils.